Penjatuhan Putusan Pidana Bersyarat dalam Mencapai Tujuan Pemidanaan dalam Sistem Peradilan Pidana (Studi di Pengadilan Negeri Marisa) - Nusa, Nuryanto D.; Ismail, Nurwita; Amu, Robby W. (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The purpose of this research is to find out and analyze the basis of the judge's consideration in imposing a conditional criminal sentence at the Marisa Court, Pohuwato Regency and to find out and analyze the provisions of conditional punishment in achieving the objectives of punishment in the Indonesian punishment system. The implementation of this research is empris research. In this study, researchers used a qualitative method. The consideration of judges in imposing conditional criminal decisions is a complex and diverse process. It involves an evaluation of the offender's circumstances, community safety, rehabilitation needs, as well as the effectiveness of the punishment in preventing future law violations. By carefully considering these factors, judges can make fair and effective decisions. The judiciary is known as the mouthpiece of the law. Conditional punishment in the Indonesian punishment system can be implemented where the Judge can set a general condition, namely that the convicted person during the specified probation period will not commit a criminal act, and a special condition, which is specifically aimed at the behavior of the convicted person. Conditional punishment can be imposed if the Judge imposes a maximum imprisonment of 1 (one) year.  Conditional punishment is an important instrument in the Indonesian punishment system because it provides an opportunity for criminal offenders to rehabilitate themselves and avoid re-engaging in criminal activities.